2016
DOI: 10.1097/igc.0000000000000765
|View full text |Cite
|
Sign up to set email alerts
|

Modified Gluteal Fold V-Y Advancement Flap for Reconstruction After Radical Vulvectomy

Abstract: The V-Y cutaneous suprafascial gluteal advancement flap for vulvar reconstruction after vulvectomy is an easy, safe, and reliable procedure. However, even mild local scar defect after bilateral flap may impact on wound healing and hospital stay, in elderly and ASA3 patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…One disadvantage of the ALT flap may be color match. Although no studies have directly compared the donor site morbidity of these various options and the ALT flap, their overall rates of complications appear to be comparable and in the range of 10–20%, with all options having a minimal effect on functional outcomes (Benedetti Panici et al, 2014; Chang et al, 2016; Collins, Ayeni, & Thoma, 2012; Conri et al, 2016; Hanasono, Skoracki, & Yu, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…One disadvantage of the ALT flap may be color match. Although no studies have directly compared the donor site morbidity of these various options and the ALT flap, their overall rates of complications appear to be comparable and in the range of 10–20%, with all options having a minimal effect on functional outcomes (Benedetti Panici et al, 2014; Chang et al, 2016; Collins, Ayeni, & Thoma, 2012; Conri et al, 2016; Hanasono, Skoracki, & Yu, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…No necrosis of the flaps were observed. (Conri et al, 2016). Additionally, in another case series of 5 patients with 7 V-Y advancement flaps, one patient had partial dehiscence after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…(Conri et al, 2016). Their cohort of patients was operated and cared for in the French healthcare system and the patients remained in the hospital until local scar defects were healed to allow for inpatient postoperative nursing care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Nakamura et al, 2010) Conri et al found VeY suprafascial gluteal advancement flaps to be safe options for a reliable reconstruction of vulvar defects despite ASA score, age, or BMI. (Conri et al, 2016). Their cohort of patients was operated and cared for in the French healthcare system and the patients remained in the hospital until local scar defects were healed to allow for days1 (0-7) Area of Defect (cm 2 ) 3 0 ( 6 -131) EBL (mL) 50 (5-400) Total Operative Time minutes179 (50-315) Hospital Stay days3 1-7cm 2 = centimeter 2 , mL = milliliters, min = minute.…”
Section: Discussionmentioning
confidence: 99%